2013
DOI: 10.1038/nm.3418
|View full text |Cite
|
Sign up to set email alerts
|

Self-renewal as a therapeutic target in human colorectal cancer

Abstract: Tumor recurrence following treatment remains a major clinical challenge. Evidence from xenograft models and human trials indicates selective enrichment of cancer-initiating cells (CICs) in tumors that survive therapy. Together with recent reports showing that CIC gene signatures influence patient survival, these studies predict that targeting self-renewal, the key 'stemness' property unique to CICs, may represent a new paradigm in cancer therapy. Here we demonstrate that tumor formation and, more specifically,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
455
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 444 publications
(475 citation statements)
references
References 42 publications
19
455
1
Order By: Relevance
“…In cancer cell lines, we have observed that miR-215 expression can both inhibit the clonogenicity and promote the adoption of differentiated morphologies. Indeed, a recent study by Kreso et al demonstrated strikingly similar effects of small-molecule inhibition and siRNA knockdown of BMI1 in CRCs in vitro (43). Further studies of the role of miR-215 in multilineage differentiation in the normal gut and in CRC will be necessary to understand more precisely the stage at which miR-215 expression is involved in promoting differentiation in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…In cancer cell lines, we have observed that miR-215 expression can both inhibit the clonogenicity and promote the adoption of differentiated morphologies. Indeed, a recent study by Kreso et al demonstrated strikingly similar effects of small-molecule inhibition and siRNA knockdown of BMI1 in CRCs in vitro (43). Further studies of the role of miR-215 in multilineage differentiation in the normal gut and in CRC will be necessary to understand more precisely the stage at which miR-215 expression is involved in promoting differentiation in vivo.…”
Section: Discussionmentioning
confidence: 95%
“…S3 C and D). Furthermore, silencing ROR1 reduced expression of Bmi-1, the polycomb ring-finger oncogene that regulates CSC self-renewal (38,39). Moreover, silencing ROR1 protein expression inhibited the expression level of EMT markers (e.g., N-cadherin and vimentin) and SNAIL1/2, master regulators of EMT (Fig.…”
Section: Silencing Expression Of Ror1 Reduces Ovarian Cancer Cell Expmentioning
confidence: 87%
“…BMI-1 expression has been associated with aggressive colon cancer and poor patient outcome, and also mediates chemotherapy and radiation resistance (50). One notable study demonstrates success in specifically exploiting stem cell self-renewal as a therapeutic target, thereby providing the basis for a new therapeutic approach in CRC treatment (51). Data from this study demonstrate that tumor formation and human colorectal CSC function are dependent on the self-renewal regulator BMI-1.…”
Section: Colorectal Cscs and Targeted Therapymentioning
confidence: 75%
“…Downregulation of BMI-1 reduced human colorectal cancer growth and inhibited the ability of colorectal CSCs to self-renew, resulting in decreased tumorigenic potential. In addition, the BMI-1 inhibitor irreversibly impaired colorectal CSCs (51). Following the success of this study, future studies should focus on additional molecules and gene signatures that underlie stemness.…”
Section: Colorectal Cscs and Targeted Therapymentioning
confidence: 75%